mitoTALEN reduces the mutant mtDNA load in neurons - Sandra R. Bacman; Jose Domingo Barrera-Paez; Milena Pinto; Derek Van Booven; James B. Stewart; Anthony J. Griswold; Carlos T. Moraes (Elsevier, 2024)
Mutations within mtDNA frequently give rise to severe encephalopathies. Given that a majority of these mtDNA defects exist in a heteroplasmic state, we harnessed the precision of mitochondrial-targeted TALEN (mitoTALEN) to selectively eliminate mutant mtDNA within the CNS of a murine model harboring a heteroplasmic mutation in the mitochondrial tRNA alanine gene (m.5024C>T). This targeted approach was accomplished by the use of AAV-PHP.eB and a neuron-specific synapsin promoter for effective neuronal delivery and expression of mitoTALEN. We found that most CNS regions were effectively transduced and showed a significant reduction in mutant mtDNA. This reduction was accompanied by an increase in mitochondrial tRNA alanine levels, which are drastically reduced by the m.5024C>T mutation. These results showed that mitochondrial-targeted gene editing can be effective in reducing CNS-mutant mtDNA in vivo, paving the way for clinical trials in patients with mitochondrial encephalopathies.